2020
DOI: 10.1007/s11095-019-2751-z
|View full text |Cite
|
Sign up to set email alerts
|

Counterion of Chitosan Influences Thermodynamics of Association of siRNA with a Chitosan-Based siRNA Carrier

Abstract: Purpose:The work aimed to compare quality of a siRNA carrier prepared with chitosan of two different sources having similar degree of deacetylation and molecular weights. Differences were analyzed from thermodynamic characteristics of interactions with siRNA. Methods: The siRNA carrier (chitosan-coated poly(isobutylcyanoacrylate) nanoparticles) was prepared with home-prepared, CS Lab , and commercial, CS Com , chitosans. Chitosan counterion was identified and chitosans CS Com mod1 and CS Com mod2 were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Chitosan was purified preparing a solution at 2 g in 50 cm 3 of hydrochloric solution 0.1M that was dialyzed (Spectra/Por ® membrane, MWCO 3 500g/mol) against 1 L of hydrochloric acid solution (0.1 N) twice for 1 h and once overnight. Purified chitosan was recovered after frozen at -20 °C by lyophilization in an Alpha 1-2 LD plus lyophilizator (Bioblock Scientific) for 24 h. This chitosan was associated with a chloride counter ion (13.9% in weight as determined by elemental analysis) (Zandanel et al, 2020). The degree of deacetylation was 92% as determined by RMN (Zandanel et al, 2020) The purified mucins from porcine stomach were used a model of mucins in the ITC experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan was purified preparing a solution at 2 g in 50 cm 3 of hydrochloric solution 0.1M that was dialyzed (Spectra/Por ® membrane, MWCO 3 500g/mol) against 1 L of hydrochloric acid solution (0.1 N) twice for 1 h and once overnight. Purified chitosan was recovered after frozen at -20 °C by lyophilization in an Alpha 1-2 LD plus lyophilizator (Bioblock Scientific) for 24 h. This chitosan was associated with a chloride counter ion (13.9% in weight as determined by elemental analysis) (Zandanel et al, 2020). The degree of deacetylation was 92% as determined by RMN (Zandanel et al, 2020) The purified mucins from porcine stomach were used a model of mucins in the ITC experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Purified chitosan was recovered after frozen at -20 °C by lyophilization in an Alpha 1-2 LD plus lyophilizator (Bioblock Scientific) for 24 h. This chitosan was associated with a chloride counter ion (13.9% in weight as determined by elemental analysis) (Zandanel et al, 2020). The degree of deacetylation was 92% as determined by RMN (Zandanel et al, 2020) The purified mucins from porcine stomach were used a model of mucins in the ITC experiments. The commercial preparation was dispersed in Milli-Q ® water at a concentration of 1g/L for 2 h at room temperature and frozen at -20°C as aliquots of 1 cm 3 for storage until use.…”
Section: Methodsmentioning
confidence: 99%
“…[98] When the ionization rate of chitosan is increased, either by lowering the pH or decreasing the DA, K increases too, which is expected for a complexation mechanism dominated by the electrostatics. [85] It was also shown that the siRNA sequence [8] and the nature of the counter ion associated with chitosan [105] can influence the binding affinity, which for the latter can be explained by considering the polyelectrolyte complexation as a kind of substitution reaction of counterions. [17] In general, there is a strong correlation between the binding constant and the encapsulation efficiency of siRNA in complexes.…”
Section: Thermodynamics Of Complexationmentioning
confidence: 99%
“…Corresponding experiments showed that chitin is a nontoxic and degradable polymer, with a certain ability to inhibit the growth of microorganisms 40,41 . Chitosan not only has the excellent properties of chitin, but also has other characteristics, such as being a hemostatic agent, a detoxifying agent, and a biological carrier 42‐46 …”
Section: Discovery and Preparationmentioning
confidence: 99%